Consequences of Skyrocketing Fertilizer Prices - Singerman, Ariel; Futch, Stephen (EDIS, 2022)
Chemical input prices have increased significantly during the last year. In particular, the price of fertilizer has roughly doubled during the last 12 months. Supply and demand factors (some of them resulting from Russia’s invasion of Ukraine due to the status of those two countries as global producers and exporters of fertilizer inputs and crops) can contribute to explain such an increase. In this article, we provide estimates for the magnitude by which prices, pound solids, and/or yield would need to increase to offset the fertilizer price increase. However, since none of the three variables are under the control of growers, we hypothesize what is their likeliest reponse in terms of budget allocation.